2013
DOI: 10.1142/s0218271813500892
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Alignment in Jvas/Class Flat Spectrum Radio Surveys

Abstract: We present a detailed statistical analysis of the alignment of polarizations of radio sources at high redshift. This study is motivated by the puzzling signal of alignment of polarizations from distant quasars at optical frequencies. We use a coordinate invariant measure of dispersion to test for alignment of polarizations of widely separated sources. The data from JVAS/CLASS 8.4 GHz surveys are used for our study. We find that the data set with polarization flux greater than 1 mJy shows a significant signal o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 52 publications
(101 reference statements)
6
31
0
Order By: Relevance
“…Another possibility is that sources in a small neighbourhood are observed together within a particular observational run. It is possible that this could generate alignment in sources within small angular separations, as observed in Tiwari & Jain (2013). We cannot rule out such a possibility.…”
Section: Datamentioning
confidence: 94%
See 3 more Smart Citations
“…Another possibility is that sources in a small neighbourhood are observed together within a particular observational run. It is possible that this could generate alignment in sources within small angular separations, as observed in Tiwari & Jain (2013). We cannot rule out such a possibility.…”
Section: Datamentioning
confidence: 94%
“…The polarization data is likely to have large scatter and we use the jackknife estimate of errors. The jackknife errors are found to be large in comparison to the squared variance of alignment statistics of shuffled PAs (Tiwari & Jain 2013). In our earlier determination of the significance of alignment we had used the latter procedure (Tiwari & Jain 2013).…”
Section: Extracting Spectral Index Of Intergalactic Magnetic Field Frmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant signal was detected in this sample either. However, Tiwari & Jain (2013) and Pelgrims & Hutsemékers (2016) used largely the same JVAS and CLASS data and presented evidence for the global alignment of polarization vectors in their sample. Moreover, Pelgrims & Hutsemékers (2016) demonstrated that the radio polarization position angles of the quasars are aligned with the axes of the large quasar groups they belong to.…”
Section: Introductionmentioning
confidence: 99%